Manuales teológicos según el Plan Educativo de 1852 = Abweichender Titel: Theological Manuals according to the Educational Plan of 1852 - González Lozano, Francisco (Cauriensia, 2025)
The theology manuals are texts that have served for the formation of the students who studied in the seminaries; educational institutions that emerged after the achievement of the Council of Trent in order to give a comprehensive and homogeneous training to candidates for the priesthood, which at that time was somewhat lax. Taking into account that not all the students who went through the seminaries became priests, the work of these entities was very important in relation to the promotion of culture and education in the places where they were developed. Since the mid-17th century, the State has actively participated in the educational organization of these centers, leaving its mark on each of its actions. The curriculum of 1852 is a faithful proof of this. In the present study we will analyze the texts that were used in the seminaries in the first educational stage, that is, the one related to Theology to better understand the educational processes in force in Spain in the mid-nineteenth century.